Membangun Kesadaran Lingkungan melalui Edukasi Pengelolaan Sampah serta Pembuatan Peta Administrasi dan Profil Dusun di Padukuhan Nganti - Habibi, Maulia Muhammad; Nugroho, Revaldo Septian; Fadhila, Azkia; Arbah, Azmi Isnaeni; Pramesti, Tri Nita; Wibowo, Diana Putri; Husna, Raudhatul; Pramana, Indra; Purnama, Muhammad Raihan; Hermawan, Ongki Hermawan (Universitas Muhammadiyah Yogyakarta, 2025)
The development of the times brings various challenges and issues into focus, one of which is environmental problems. An example of this can be seen in Padukuhan Nganti, Kulon Progo Regency, Yogyakarta Special Region. Therefore, there is a need to raise awareness among the community itself. This community service program aims to raise awareness among the residents of Padukuhan Nganti regarding waste management and to systematically document the village’s identity. The main programs implemented include waste management socialization and TPS (Temporary Disposal Site) proposal, the creation of an administrative map and information board (mading) of the village, as well as documentation in the form of a documentary video and a village profile article. Through this program, the community is expected to gain a better understanding of environmentally friendly waste management and have access to administrative data that can be utilized for village development purposes. The implementation method began with waste management socialization, involving local residents, followed by the preparation and submission of a TPS proposal letter to the relevant authorities. The creation of the administrative map was carried out through direct surveys and interviews with residents to determine territorial boundaries and strategic locations. The collected data was used to compile the village information board (mading), which was installed in a strategic location to facilitate access to information for both residents and tourists. Village identity documentation was conducted through a documentary video showcasing the history, culture, and economic potential of the village, as well as a village profile article uploaded to a digital platform as an official reference for administrative purposes and village development assistance proposals. The results of this program indicate that all activities have been successfully carried out. The waste management socialization was attended by approximately 40 residents and successfully increased community awareness of community-based waste management. The administrative map and information board provided clearer information regarding territorial boundaries and public facilities. The documentary video and village profile article received positive responses from the community and serve as promotional tools for local potential, which can be utilized for future village development. With this program, it is hoped that the community will become more proactive in maintaining environmental sustainability and utilizing documented administrative information to support sustainable village development